Editorial - Aguirre Chávez, Felipe (2021)
In the current year 2021, the bicentennial of the proclamation of Peru's independence, Brother Pablo González Franco, rector of our university, wrote in a significant letter marking the start of academic activities: "It is our duty to celebrate these anniversaries in the midst of a difficult situation. We live in a complex, conflictive, and fractured environment, in a turbulent world. At this challenging start of 2021, more than confrontational men and women, we need to be cooperative people; more than foments of sterile conflicts, we need to be guiding beacons, beacons of light and hope."